Pediatric acute respiratory distress syndrome associated with human metapneumovirus and respiratory syncytial virus. Issue 7 (7th May 2018) - Ravindranath, Thyyar M.; Gomez, Amanda; Harwayne‐Gidansky, Ilana; Connors, Thomas J.; Neill, Nathan; Levin, Bruce; Howell, Joy D.; Saiman, Lisa; Baird, John S.
Abstract: Objectives: To study the incidence, risk factors, clinical course, and outcome of ARDS in children with HMP and RSV. Working Hypothesis: We hypothesized that ARDS in children with HMP was similar in incidence, risk factors, clinical course, and outcomes to ARDS in children with RSV. Study Design: Retrospective, observational study over 2 years. Patient‐Subject Selection: Patients included were <18 years old with HMP or RSV detected from nasopharyngeal specimens by commercial reverse transcriptase polymerase chain reaction assay admitted to a study site. Methodology: We described the incidence of ARDS within 1 week following the detection of HMP or RSV using recently developed Pediatric ARDS (PARDS) criteria. We also assessed risk factors, clinical course, and outcomes of children in the PICU with HMP or RSV and PARDS or non‐PARDS. Results: We identified 57 patients with HMP and 161 patients with RSV: the proportions of patients with either virus who developed PARDS (HMP: 23%, RSV: 20%) and severe PARDS (HMP: 9%, RSV: 7%) were similar, as were the proportions of patients with acute (or acute‐on‐chronic) respiratory failure who developed PARDS (HMP: 41%, RSV: 31%). In a logistic regression model, risk factors associated with PARDS included neurologic comorbidity and PIM 3 probability of mortality, but not virus type. The risk factors, clinical course, and outcomes were similar for patients with PARDS associated with HMP and RSV. Conclusions: About 1/3 of children with HMP or RSV and acute (or acute‐on‐chronic) respiratory failure developed PARDS. Children with either virus and a neurologic comorbidity or an increased PIM 3 probability of mortality were at increased risk for PARDS.